Gender Differences in Attitudes Toward Premarital Health Screening Compliance: Perbedaan Gender dalam Sikap terhadap Kepatuhan Pemeriksaan Kesehatan Pranikah - Yusmi Putri Irma Khimayatillah; Paramitha Amelia Kusumawardani; Sri Mukhodim Farida Hanum; Siti Cholifah (Academia Open, 2023)
Background: Premarital health checks are essential for future spouses to ensure a healthy family start. Specific Background: Although required for marriage registration, premarital health screenings are often overlooked. Knowledge Gap: Research on attitudes toward these screenings, especially for prospective grooms, is scarce. Aims: This study examines the link between attitudes and participation in premarital health checks. Methods: A cross-sectional study of 30 prospective couples in Pakis Health Center, Surabaya, was conducted in October-November 2022. Results: Findings show a positive association between male attitudes and screening participation (p=0.024), while female attitudes showed no significant link (p=0.143). Novelty: The study reveals gender-specific attitude influences on health check participation. Implications: Tailored education could increase compliance, benefiting family health planning. Highlights: Male attitudes showed a positive link with screening participation, unlike female attitudes. Gender differences indicate the need for targeted health education. Premarital health checks support healthier family planning and reduce health risks. Keywords: Premarital Health Checks, Attitudes, Prospective Couples, Health Screening, Gender Differences